Detection of 2-eicosanol by gas chromatography-mass spectrometry in sputa from patients with pulmonary mycobacterial infections. - Alugupalli, S (1993)
A total of 96 sputum specimens from patients with suspected or known mycobacterial and nonmycobacterial pulmonary infections were analyzed by gas chromatography-mass spectrometry for the presence of 2-eicosanol. This secondary alcohol was detected in all of the 25 sputum specimens culture positive for Mycobacterium tuberculosis, in 7 of the 9 sputum specimens culture positive for M. avium complex, and in all 3 of the studied sputum specimens associated with M. malmoense. The alcohol was not detected in any of the 45 culture-negative sputum specimens or in 14 sputum specimens culture positive for Staphylococcus aureus, Pseudomonas aeruginosa, Haemophilus influenzae, and Streptococcus pneumoniae. The ratio of tuberculostearic acid to 2-eicosanol was much lower in sputum samples culture positive for mycobacteria than in the corresponding in vitro-grown cultures. The present findings indicate that 2-eicosanol may be useful as a chemical marker for rapid diagnosis of pulmonary infections caused by the M. avium complex, M. malmoense, and M. tuberculosis.